2022
DOI: 10.1038/s42004-022-00726-z
|View full text |Cite
|
Sign up to set email alerts
|

The ability of trimethylamine N-oxide to resist pressure induced perturbations to water structure

Abstract: Trimethylamine N-oxide (TMAO) protects organisms from the damaging effects of high pressure. At the molecular level both TMAO and pressure perturb water structure but it is not understood how they act in combination. Here, we use neutron scattering coupled with computational modelling to provide atomistic insight into the structure of water under pressure at 4 kbar in the presence and absence of TMAO. The data reveal that TMAO resists pressure-induced perturbation to water structure, particularly in retaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 96 publications
(134 reference statements)
2
16
0
Order By: Relevance
“…A key function of these osmolyte adaptations is to maintain an optimal balance between biomacromolecular stability and flexibility, a balance that is crucial to optimal physiological function . In this respect, TMAO appears to play a particularly potent role . The TMAO concentration in the muscle tissue of teleosts (bony fishes with ray fins) and chondrichthyes (jawed fishes with cartilaginous skeletons) have been found to increase with increasing capture depth in the ocean, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key function of these osmolyte adaptations is to maintain an optimal balance between biomacromolecular stability and flexibility, a balance that is crucial to optimal physiological function . In this respect, TMAO appears to play a particularly potent role . The TMAO concentration in the muscle tissue of teleosts (bony fishes with ray fins) and chondrichthyes (jawed fishes with cartilaginous skeletons) have been found to increase with increasing capture depth in the ocean, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…20 In this respect, TMAO appears to play a particularly potent role. 98 The TMAO concentration in the muscle tissue of teleosts (bony fishes with ray fins) and chondrichthyes (jawed fishes with cartilaginous skeletons) have been found to increase with increasing capture depth in the ocean, i.e., with increasing hydrostatic pressure, which is why TMAO is also referred to as a "piezolyte". 20,53 In addition, by altering the crowded interior of the cell, living systems gain an additional means to control their protein and nucleic acid machinery, a level of control exerted close to the thermal fluctuations on the order of k B T that can help suppress deteriorating effects of external stressors such as HHP and confer additional fitness to cells.…”
Section: Volume-sensitive Conformational Changes Phase Transitions An...mentioning
confidence: 99%
“…EPSR therefore provides atomistic information to produce a complete set of partial structure factors by building a simulation that is simultaneously constrained by experimental data on fewer distinct isotopic variants (typically between 3 and 7) . Neutron scattering combined with EPSR has previously been well applied to the study of simple binary solutions, including those containing biomolecule building blocks such as amino acids ,, and short peptides, as well as a host of other aqueous systems including pure water under various pressures and temperatures, , alcohols, salts, , and other osmolytes. EPSR builds a simulated box of molecules matching the concentrations and density of the experimental sample, with each atom characterized by a reference potential consisting of a charge q and the Lennard–Jones (LJ) parameters σ and ε using the standard Lorentz–Berthelot mixing rules. Exchangeable hydrogens are accounted for when calculating the predicted weights of each interatomic correlation to the total scattering data for each isotopic variant.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 Reports have suggested that despite this stabilizing effect, osmolytes of different structural classes interact through diverse mechanisms ranging from preferential exclusion of water bodies to separation of folding phases or even binding to the transition state, adding further complexity to their mode of action. [11][12][13][14][15][16] Since the mechanical stability of proteins is an indispensable aspect of characterizing their folding phenomena, it is plausible that these osmolytes could affect protein folding by modulating their stability under force. Therefore, the molecular details of such thermodynamic preferences of different osmolytes toward the folded state of proteins are intricately context-dependent and need to be fully understood.…”
Section: Introductionmentioning
confidence: 99%